ECOLOGICAL DOMINANT IN POSTMODEMIST CULTURE - Česlovas Kalenda (Problemos)
Modernism is characterised by theory and practise of a man's technocratic domination over nature based on the principles of scientific rationalism and utilitarianism. One of essential features of postmodernistic culture is formation of a new relationship with natural reality. The article deals with anti-modernistic philosophical and ethical conceptions (A. Leopold, E. Schumacher, B. Callicott, O. Marquard) which are significant for formulation of a new paradigm of civilisation evolution, establishment of ecological priority against economics, development of ecological ethics.